Application of genre-based approach in teaching writing to 10th form students: action research at Sơn Dương high school, Tuyen Quang province = Nghiên cứu hành động về áp dụng phương pháp dạy viết dựa vào thể loại cho học sinh lớp 10, trường THPT Sơn Dương, Tỉnh Tuyên Quang. - Nguyễn, Thị Vân Anh (2020)
This research was carried out in an attempt to solve the problems of students’ poor writing performance at Sơn Dương High School. A hypothetical solution – the use of genre-based approach to teach writing – was tested in this study through a small-scale action research project. The study was conducted in the form of an action research, with the participation of 38 students from class 10A1